2017
DOI: 10.1002/eji.201646716
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β regulation of encephalitogenic and regulatory T cells in multiple sclerosis

Abstract: Transforming growth factor-beta (TGF-β) is a pleiotrophic cytokine that has been shown to influence the differentiation and function of T cells. As such, the role that TGF-β plays in immune-mediated disease, such as multiple sclerosis (MS), has become a major area of investigation since CD4 T cells appear to be a major mediator of the autoimmunity. This review analysis the literature on the role that TGF-β plays in the generation and regulation of encephalitogenic T cells in experimental autoimmune encephalomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 86 publications
7
63
0
1
Order By: Relevance
“…Since MS is an autoimmune disorder characterized by neuronal damage, demyelination, and chronic inflammation, it seems that cytokines are significant inflammation mediators. In particular, IL-27 and TGFβ modify inflammation and can be secreted directly at inflammatory sites in the CNS during MS [16,24]. In agreement with this paper's findings, Tang et al [7] explored the role of IL-27 in MS patients and reported that plasma and mRNA expression levels of IL-27 had declined in MS patients.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since MS is an autoimmune disorder characterized by neuronal damage, demyelination, and chronic inflammation, it seems that cytokines are significant inflammation mediators. In particular, IL-27 and TGFβ modify inflammation and can be secreted directly at inflammatory sites in the CNS during MS [16,24]. In agreement with this paper's findings, Tang et al [7] explored the role of IL-27 in MS patients and reported that plasma and mRNA expression levels of IL-27 had declined in MS patients.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, more studies reported that IL-27 could quell inflammation state through prohibiting the function and the differentiation of Th17 cells, particularly repression to the secretion of IL-17A via JAK1-STAT1 [36], followed by ameliorated clinical symptoms and development of MS disease [11,19,35]. Various studies have illustrated the role of TGF-β1 in inciting the production of IL-10 [32,37,38], and also, it has become elucidated that TGF-β1 can trigger IL-10 through Smad4 pathway [16]. Following the same issue, TGF-β1 could repress the differentiation of naive CD4+ T cells into pathogenic Th17 ones and down-regulate the mRNA expression of IL-17 due to the immunosuppressive traits [39][40][41].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 contributes to the protection of our body against the auto-reactive T cells by increasing the differentiation of CD4+ T cells into Treg cells. TGF-β also prevents differentiation of CD4+ T cells towards Th1, which leads to a decrease in IFN-γ production and induction of EAE [29]. TGF-β1 has various effects, especially protective one in the context of MS/ EAE.…”
Section: Discussionmentioning
confidence: 99%
“…The use of TGF-β may be an alternative aid in the treatment of multiple sclerosis, since Treg and effector T cells are defective. The causes of multiple sclerosis are still unknown, but the immune system plays a central role in the development of the disease [98,99].…”
Section: Rheumatoid Arthritis and Multiple Sclerosismentioning
confidence: 99%